Dynamic development of municipal bonds on capital markets in Romania and contribution to regional development - Ciprian Antoniade Alexandru (European Regional Science Association (ERSA), 2011)
Investment demand for regional economic development led to the use of increasingly diversified financial instruments. The local authorities in the capital market were achieved through municipal bonds, the most used financial vehicle in the category of fixed income instruments. In this paper is presented results of research on the use of municipal bonds to finance projects on local or regional level in Romania. Among the research results is included determining the degree of correlation between risk and return of financial instruments, but also a possible causal link between the amount of investments by region and degree of development of the region. In conclusion are shown several views on the use of municipal bond into investment portfolio management from investment funds from Romania.
Keywords: 330